2021
DOI: 10.1111/ecc.13515
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of technology‐based psychosocial interventions for child, adolescents and young adults undergoing cancer treatment: A meta‐analysis of randomised controlled trials

Abstract: Background Cancer can have various psychosocial effects on children and young adults. Technology‐based psychosocial interventions are increasingly popular in paediatric oncology for psychosocial health. Objective The objective of this study is to investigate the effectiveness of technology‐based psychosocial interventions applied to children, adolescent and young adults undergoing cancer treatment. Methods Eight electronic databases including PubMed, Cochrane Library (including Cochrane Central Register of Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“… 15 In the meta-analysis of Sari Ozturk and Toruner, technology-based psychosocial interventions are effective in reducing anger, anxiety, and depression in children with cancer. 34 Also, in the meta-analysis of Contreras et al., technology-based parenting programs have positive effects on emotional well-being of parents of children with cancer. 31 In this context, technology-based interventions are considered to be an effective approach to support children with cancer and their parents.…”
Section: Discussionmentioning
confidence: 99%
“… 15 In the meta-analysis of Sari Ozturk and Toruner, technology-based psychosocial interventions are effective in reducing anger, anxiety, and depression in children with cancer. 34 Also, in the meta-analysis of Contreras et al., technology-based parenting programs have positive effects on emotional well-being of parents of children with cancer. 31 In this context, technology-based interventions are considered to be an effective approach to support children with cancer and their parents.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our systematic review is one among several reviews of interventional studies (Coughtrey et al, 2018;Ozturk & Toruner, 2022;Pai et al, 2006;Ramsey et al, 2020;Seitz et al, 2009;Zhang et al, 2021) conducted to evaluate the effects of psychosocial interventions on the psychological, physical, and social outcomes of children with cancer. Nevertheless, most of the previous reviews included studies that evaluated both children and young adult participants (Coughtrey et al, 2018;Ozturk & Toruner, 2022;Ramsey et al, 2020;Seitz et al, 2009;Zhang et al, 2021), and/or any types of interventional studies (Ramsey et al, 2020;Seitz et al, 2009;Zhang et al, 2021). However, as children are physiologically and developmentally different from adults, the effects of psychosocial interven- In our review, the majority of included trials reported improvements in health outcomes of the experimental groups compared to control groups and were consistent with previous reviews (Coughtrey et al, 2018;Ramsey et al, 2020;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our systematic review is one among several reviews of interventional studies (Coughtrey et al, 2018; Ozturk & Toruner, 2022; Pai et al, 2006; Ramsey et al, 2020; Seitz et al, 2009; Zhang et al, 2021) conducted to evaluate the effects of psychosocial interventions on the psychological, physical, and social outcomes of children with cancer. Nevertheless, most of the previous reviews included studies that evaluated both children and young adult participants (Coughtrey et al, 2018; Ozturk & Toruner, 2022; Ramsey et al, 2020; Seitz et al, 2009; Zhang et al, 2021), and/or any types of interventional studies (Ramsey et al, 2020; Seitz et al, 2009; Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations